2018
DOI: 10.1017/s0007114518003379
|View full text |Cite
|
Sign up to set email alerts
|

Not all forms of dietary phosphorus are equal: an evaluation of postprandial phosphorus concentrations in the plasma of the cat

Abstract: Phosphorus is present in diets as naturally occurring P from raw materials or added as an inorganic salt. However, little is known about postprandial kinetics of P absorption in cats. Here, we describe several studies quantifying postprandial kinetics following the ingestion of diets of varying composition. Briefly, cats were fed a meal consisting of 50 % of their metabolic energy requirement in a randomised crossover design. A pre-meal baseline blood sample was taken via cephalic catheter and repeated measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 57 publications
5
58
0
2
Order By: Relevance
“…This led to structural and functional changes in the kidneys as indicated by reduced GFR and proteinuria, compatible with early stage CKD. (2) This may have been due to the high postprandial serum phosphate levels induced by the test diet (7) . In a subsequent 28-week study, exposure to a more moderate level of SDHP, providing 1.5g/1000kcal P (total P 3.6g/1000kcal; Ca:P 0.9) resulted in the development of renoliths and/or structural changes in the kidneys (2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to structural and functional changes in the kidneys as indicated by reduced GFR and proteinuria, compatible with early stage CKD. (2) This may have been due to the high postprandial serum phosphate levels induced by the test diet (7) . In a subsequent 28-week study, exposure to a more moderate level of SDHP, providing 1.5g/1000kcal P (total P 3.6g/1000kcal; Ca:P 0.9) resulted in the development of renoliths and/or structural changes in the kidneys (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Dietary P from organic raw materials, such as meat and bone meals or plant-based ingredients, has been shown to be less bioavailable than from soluble P salts (6; 10) . Recent studies in healthy adult cats investigating post-prandial responses following single meal exposure indicate that soluble P salts, but not organic P sources, induce rapid, dose-dependent increases in serum phosphate and parathyroid hormone (PTH), a key regulator of mineral homeostasis (7) . There is also evidence that increasing the Ca:P may mitigate the effects of exposure to high levels of soluble P salts in the diet (7; 11) .…”
Section: Introductionmentioning
confidence: 99%
“…While the organic form binds to proteins resulting in lower absorption, the inorganic phosphorus is absorbed much more readily, making its excess potentially more harmful to animals. Coltherd et al (2018) observed that addition of inorganic phosphorous salts in the diet at levels from 0.5 g/1,000 kcal is able to increase plasma phosphorus in cats. Meanwhile, the authors did not verify changes in plasma phosphorus concentration after the ingestion of organic phosphorus.…”
Section: Discussionmentioning
confidence: 98%
“…Coltherd et al. () observed that addition of inorganic phosphorous salts in the diet at levels from 0.5 g/1,000 kcal is able to increase plasma phosphorus in cats. Meanwhile, the authors did not verify changes in plasma phosphorus concentration after the ingestion of organic phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…These include the P source, the amount of 25‐hydroxyvitamin D, and the relative amounts of P and Ca in the food products . Previous studies have shown that organic P salts experience decreased absorption compared with inorganic P in cats . Although the adverse health effects of high dietary P have been demonstrated, there are no published studies to date evaluating the safety in cats of foods with high organic P. Also, the absorption of phosphorus in any form is impacted by other minerals, notably Ca, where a high Ca:P ratio decreases P absorption .…”
Section: Discussionmentioning
confidence: 99%